Satisfaction of Hearing Aids Users With Hearing Loss of Severe and Deep Degree - Lessa, Alexandre Hundertmarck (International Archives of Otorhinolaryngology, 2010)
Introduction: It is necessary to analyze the efficiency of the hearing aids use, considering the necessity of enlargement and communication difficulty. Objective: To analyze the satisfaction of adults and elders, users of hearing aids with hearing loss of severe and deep degree, using a questionnaire and searching factors that can difficult the adaptation. Method: A retrospective study of 56 patients, with age group between 18 and 86 years old, hearing loss of severe and deep degree and users of HA by a program of concession of hearing aids, submitted to the questionnaire: "Satisfaction with Amplification in Daily Life". The global average was calculated by sub scale and by question and it was given emphasis to the questions that resulted in best and worse averages. Results: 58,9% were women and 41,1% men, about of 55% of the patients presented hearing loss of severe degree and 45% deep degree. 87,5% referred use major than 8 hours daily. The users believe that the acquisition of the hearing aid was the best option and this aid very much in the speech understanding. They feel themselves trustful and able with the sounding amplification and refer a good service by professionals of the service. The performance to the telephone was the problem found. Conclusion:It was demonstrated high degree of satisfaction in the studied population. The hearing loss degree, as well as the incompatibility of systems between telephone and telecoils and the difficulty in the placement of telephone ate factors that difficult the good performance to the telephone. The accentuated hearing loss collaborate for the hearing aid be an integral part of the daily life and essential in the aid to the communication. ACTRN12610000424000